The relationship between the metal dusting mechanism and the synthesis of carbon nanofilaments using toluene and a nickel based alloy - Ramalall, Dawlall Shahil (My University, 2016)
Metal dusting (MD) is a severe type of corrosion that occurs mainly in petrochemical industries. The occurrence of MD is mainly due to syngas attacking Fe-, Ni- and Co-based alloys at elevated temperatures. More recently, literature has shown that apart from syngas, liquid hydrocarbon sources have been causing problems on platformer units in refineries. In the first part of this study a highly corrosion resistant Ni-based alloy (Hastelloy C276), in its polished form, was subjected to MD conditions at 800 °C using a liquid hydrocarbon (toluene) and helium (carrier gas) for 1 h. Exposure to these conditions revealed the formation of carbon nanofilaments and graphite layers which were confirmed by laser Raman spectroscopy, scanning electron microscopy (SEM) and electron probe microanalysis (EPMA). Burning off the carbon nanofilaments and the graphite layers in laboratory air for 1 h at 800 °C revealed that pits were formed on the Hastelloy C276. These same pits were not evident when Hastelloy C276 was exposed to either the carrier gas (helium) or laboratory air alone. Besides MD being a continuous problem in industry, this mechanism has been shown to be beneficial in the synthesis of carbon nanofilaments viz., carbon nanofibers (CNTs) and nanotubes (CNFs). In the second part of this study, unpolished Hastelloy C276 blocks (as opposed to polished blocks) were used to synthesize carbon nanofilaments. This was done as prior studies had shown that carbon nanofilaments were produced with better quality and greater yields this way. Here the flow rate (80, 160 and 240 mL/min) and reaction duration (10, 15, 30, 45, 60, 120 and 240 min) were studied using toluene (a liquid hydrocarbon). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to assess the quality and quantity of the carbon nanofilaments synthesized. Besides the formation of carbon nanofilaments, a less important material known as graphite particle structures (GPSs) were also synthesized. These studies collectively showed that MD had taken place on the surface of Hastelloy C276 when exposed to toluene at 800 °C.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2016.
Keywords: Metals--Effect of high temperatures on; Carbon nanotubes; Nickel alloys; Corrosion and anti-corrosives; Metals